1999
DOI: 10.1063/1.371276
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of nitridated sapphire surfaces by x-ray photoelectron spectroscopy

Abstract: The characteristics of an amorphous oxynitride layer formed by nitridation are studied with x-ray photoelectron spectroscopy in order to reveal the role of nitridation before GaN growth in metalorganic chemical vapor deposition. The intensity variation of the N 1s peak with nitridation time is analyzed quantitatively using a diffusion-based model. The effective diffusion coefficient of nitrogen-related species in the amorphous layer is estimated to be 4×10−18 cm2/s at 1000 °C. The thickness of the amorphous la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…Ex situ measurements have been extensively used to study the nitridation process under different chemical processing conditions. 2,3,7,[10][11][12]15,18,23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ex situ measurements have been extensively used to study the nitridation process under different chemical processing conditions. 2,3,7,[10][11][12]15,18,23 …”
Section: Resultsmentioning
confidence: 99%
“…The normalized concentration of N 1s and O 1s was calculated from the XPS peak area divided by the corresponding atomic sensitivity factor ͑ASF͒ and normalized with the Al 2p peak area. The Al 2p peak was commonly used as a reference in sapphire nitridation studies 4,[11][12][13][14][15][16][17][18][19] since the vapor pressure of aluminum containing species ͑e.g., AlO, Al 2 O, and Al͒ is negligible at 1100°C. 24 The concentration of surface aluminum atoms was assumed therefore to be approximately constant before and after nitridation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that a thin layer of AlN is formed during this step [78,79]. In fact, the growth of an AlN [80] or a low temperature GaN [81][82][83] buffer layer has been intentionally introduced at the initial stage to improve crystal quality.…”
Section: The Aspect Of Gan Epitaxy Substrate Selectionmentioning
confidence: 99%
“…A step at the interface is observed in this figure though the atomic interfacial structure cannot be clearly observed most lightly because of sapphire surface rugosity. These stepped interfaces may be a result of the large nitridation time on the sapphire [32,33].…”
Section: Epitaxial Relationship Between the A-plane Gan And R-plane Smentioning
confidence: 99%